2019
DOI: 10.3390/jcm8091485
|View full text |Cite
|
Sign up to set email alerts
|

Association between Albumin-Bilirubin Grade and Non-Protein Respiratory Quotient in Patients with Chronic Liver Diseases

Abstract: We sought to elucidate the relationship between albumin-bilirubin (ALBI) grade and non-protein respiratory quotient (npRQ) calculated by indirect calorimetry in chronic liver disease (CLD) patients (n = 601, median age = 63 years). Factors linked to npRQ < 0.85, which is reported to be an optimal cutoff point for the prognosis in liver cirrhosis (LC) patients, were also investigated using univariate and multivariate analyses. The median npRQ for all cases was 0.86. In total, 253 patients (42.1%) had npRQ < 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…PEM is a common disorder identified in LC patients, which can cause worse clinical outcomes in LC patients [1,2,[4][5][6]8,10,11]. In our previous study, we demonstrated the significant correlation between npRQ level and albumin-bilirubin (ALBI) grade, which can be an alternative classification system for Child-Pugh classification, in patients with chronic liver diseases (CLDs) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…PEM is a common disorder identified in LC patients, which can cause worse clinical outcomes in LC patients [1,2,[4][5][6]8,10,11]. In our previous study, we demonstrated the significant correlation between npRQ level and albumin-bilirubin (ALBI) grade, which can be an alternative classification system for Child-Pugh classification, in patients with chronic liver diseases (CLDs) [12,13].…”
Section: Introductionmentioning
confidence: 99%